Modeling COVID-19 impacts and response strategies in the construction industry: PLS–SEM approach - Afiqah R., Radzi; Abdul Rahimi, Abdul Rahman; Almutairi, Saud (MDPI, 2022)
Policymakers are developing response strategies to reduce the impacts of COVID-19. However, developing response strategies without considering their relationships with the impacts of COVID-19 is ineffective. This study aims to model the causal relationships between COVID-19 impacts and response strategies in the construction industry, using Malaysia as a case study. To achieve this, a systematic literature review and semi-structured interviews with forty industry professionals were conducted, yielding 12 impacts and 22 response strategies. The impacts and strategies were inserted into a survey, and 107 valid responses were received. Exploratory factor analysis (EFA) was conducted to group the impacts and strategies. Then, partial least-squares structural equation modeling (PLS–SEM) was employed to identify the causal relationship between the impacts and strategies. The EFA results indicate that the underlying impacts are project-or material-related, and the underlying strategies are market stability and financial aid, supply chain and project support, and information and legislation. The PLS–SEM results indicate that supply chain and project support are required to address material-related impacts, and market stability and financial aid are required to address project-related impacts. This is the first paper that models the relationships between COVID-19 impacts and response strategies in the construction industry.